2016
DOI: 10.1016/j.adolescence.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the reciprocal relations between life satisfaction and social problem solving in early adolescents

Abstract: Theoretical and emerging empirical advances in the life satisfaction (LS) and social problem solving (SPS) literature suggest that LS and SPS may have bidirectional relations. The main purpose of this study was to test the hypothesis of bidirectionality between LS and two components of the SPS, orientation (SPS-O) and skills (SPS-S). Two waves of data were collected from a sample of 733 adolescents at a middle school over a 6-month period. Cross-lagged panel analysis results showed that statistically, LS signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 73 publications
2
10
0
1
Order By: Relevance
“…The CFA results confirmed the one-factor model with modification in both gender groups, consistent with the findings of a previous study (Jiang et al 2016). The multi-group CFA results revealed full scalar invariance across gender.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The CFA results confirmed the one-factor model with modification in both gender groups, consistent with the findings of a previous study (Jiang et al 2016). The multi-group CFA results revealed full scalar invariance across gender.…”
Section: Discussionsupporting
confidence: 81%
“…results showed a large parameter associated with the residual covariance of Items 3 and 4 (M.I. = 20.81), which was similar to the results in a former study (Jiang et al 2016). It seems these two items have characteristics that uniquely differ from other items.…”
Section: Single Group Confirmatory Factor Analysissupporting
confidence: 79%
See 1 more Smart Citation
“…The rationale for youth mentoring is grounded in developmental science research, where researchers found that children who have positive relationships with supportive adults fair better than those that do not (Bowen & Chapman, ; Garmezy & Masten, ; Parra, DuBois, Neville, Pugh‐Lilly, & Povinelli, ). Young people who develop relationships with supportive adults (e.g., teachers, coaches, family friends, parents) achieve higher grades, engage in less risky behaviors, and report higher levels of life satisfaction (Jiang, Lyons, & Huebner, ; Lyons, Huebner, & Hills, ; Malecki & Demaray, ). However, it is unclear what makes a relationship cohere and what makes it supportive or not, particularly in the context of structured programs that comprise the majority of efforts at formal mentoring.…”
Section: Introductionmentioning
confidence: 99%
“…So, it is logical to conclude that if one is improved, the other will get better. For this reason, both concepts must be considered to include it within future prevention and intervention of educational programs [37]. In another vein, topics such as decision making and awareness are also relevant to future Mars travels [2].…”
Section: Aspects To Include In An Educational Program On Space Travelsmentioning
confidence: 99%